Preparation of NiCr/YSZ two-layered burn-resistant coating on γ-TiAl alloys based on plasma surface metallurgy and ion plating methods - Wei, Dongbo; Li, Minfeng; Zhou, Xu; Li, Fengkun; Li, Shuqin; Zhang, Pingze (Journal of Mining and Metallurgy, Section B: Metallurgy, 2021)
The NiCr/YSZ coating was fabricated on γ-TiAl alloy by double glow plasma surface metallurgy technology and multi-arc ion plating technology. The microstructure, microhardness, bonding strength and burn resistance of NiCr/YSZ coating were studied in detail. The results showed that the NiCr/YSZ coating was dense and homogeneous, including a duplex structure of top YSZ ceramic coating and underlying Ni-Cr bond coating. The average microhardness of NiCr/YSZ coating was raised by a factor of about 2 compared to the γ-TiAl substrate. The thermal shock test indicated that the composite structure had superior bonding strength and the defects such as metal droplets on the ceramic coating were the source of cracks. The high-energy laser beam destroyed the surface of γ-TiAl alloy, forming protruding combustion products in ablation zone and splashing residues around ablation zone. When coated by NiCr/YSZ coating, the combustion process was delayed through isolating and dissipating heat. The ablation range was controlled and the ablation damage was reduced at the same irradiation power. The NiCr/YSZ coating preliminarily realized to improve the burn resistance of γ-TiAl alloy.
Keywords: γ-TiAl alloys; NiCr/YSZ coating; microstructure; bonding strength; burn resistance